Effects of Lactobacillus buchneri and Lactobacillus rhamnosus on Ryegrass Silage Fermentation and Aerobic Stability - Furong Han; Mingzhu Zhang; Wentao Sun; Changrong Wu; Yuan Huang; Guanghao Xia; Chao Chen; Fuyu Yang; Jun Hao (Fermentation)
Italian ryegrass is a high-quality forage grass, and a full understanding of the changes in its microbiome and metabolome during aerobic exposure can prolong its aerobic stability and improve its utilization value. Italian ryegrass silage was prepared with deionized water (CK), Lactobacillus rhamnosus BDy3-10 (LR), Lactobacillus buchneri TSy1-3 (LB), and a mixture of these two lactic acid bacteria (M). The silage was maintained at ambient temperature for 60 days followed by aerobic exposure. The results show that the Italian ryegrass silage in the LB and M groups exhibited aerobic stability for up to 19 days. A total of 1881 chemicals were identified in Italian ryegrass silage. These metabolites are associated with bacterial communities, especially Lactobacillus. The addition of lactic acid bacteria resulted in a common differential metabolic pathway compared to CK: “phenylpropanoid biosynthesis”. “Flavone and flavonol biosynthesis” was the significant differential metabolic pathway between LB and LR. Inoculation with LB significantly increased the concentrations of lactic acid, acetic acid, vitexin, and luteolin. In conclusion, lactic acid bacteria (LAB) additives affect the microbial community and metabolites of silage. The application of LB inoculants is a feasible way to obtain well-fermented Italian ryegrass silage and improve aerobic stability, even at higher moisture content levels.